Catalyst for air electrode, air electrode, and air secondary battery

By using a catalyst with a Mn-containing perovskite crystal structure and a second oxide, the interatomic distance is adjusted to enhance the activity of the air electrode catalyst, addressing the reduced performance issue in air secondary batteries.

JP2025009676APending Publication Date: 2025-01-20NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023184492
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2023-10-27
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

The activity per unit amount of catalyst in air electrodes is lower than the activity per unit amount of individual ORR and OER materials due to their composite ratio, leading to reduced performance in air secondary batteries.

Method used

An air electrode catalyst comprising a first oxide with a perovskite crystal structure containing Mn and a second oxide, where the interatomic distance between Mn atoms shifts to a shorter distance after heat treatment, enhancing the catalyst's activity.

Benefits of technology

The catalyst's activity per unit amount is increased, resulting in improved performance of the air electrode and air secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009676000001_ABST
    Figure 2025009676000001_ABST
Patent Text Reader

Abstract

To provide a catalyst for an air electrode, an air electrode, and an air secondary battery, capable of increasing the activity per unit amount of a catalyst as compared with the activity per unit amount of each material.SOLUTION: A catalyst for an air electrode contains a first oxide having a perovskite crystal structure containing Mn, and a second oxide. A peak existing from 0.34 nm to a 0.39 nm of an interatomic distance between an atom neighboring a Mn atom and the Mn atom in a radial distribution function determined by X-ray absorption spectroscopy becomes lower or disappears after heat treatment in an atmosphere where an oxygen partial pressure is 5.0×10-1 P or less and a temperature is 500°C or more and 800°C or less. In addition, a peak existing from 0.07 nm to 0.2 nm of the interatomic distance shifts toward a side where the interatomic distance becomes shorter after the heat treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an air electrode catalyst, an air electrode, and an air secondary battery. [Background technology]

[0002] The reaction during discharge at the air electrode of an air secondary battery is the oxygen reduction reaction (ORR), and the reaction during charge is the oxygen evolution reaction (OER), so the catalyst for the air electrode is required to have high ORR and OER activity. The prior art disclosed in Patent Document 1 combines a material with high ORR activity (ORR material) and a material with high OER activity (OER material), both of which are selected from oxides with a perovskite-type crystal structure containing Mn. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-190833 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the prior art, the content of the ORR material and the OER material per catalyst is small depending on the composite ratio of the materials, so there is a problem that the activity per unit amount of the catalyst is lower than the activity per unit amount of each material.

[0005] The present invention has been made to solve this problem, and has an object to provide an air electrode catalyst, an air electrode, and an air secondary battery that can make the activity per unit amount of the catalyst higher than the activity per unit amount of each material. [Means for solving the problem]

[0006] A first aspect for achieving this object is an air electrode catalyst comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, wherein the peak in the radial distribution function obtained by X-ray absorption spectroscopy, which exists between an atom adjacent to a Mn atom and an Mn atom at an interatomic distance of 0.34 nm to 0.39 nm, is smaller than the peak in the radial distribution function obtained by X-ray absorption spectroscopy, when the oxygen partial pressure of the air electrode catalyst is 5.0 × 10 -1 The resistance decreases or disappears after heat treatment in an atmosphere of 500°C to 800°C or less at 0.2 Pa or less.

[0007] The second aspect is an air electrode catalyst comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, wherein the peak in the radial distribution function obtained by X-ray absorption spectroscopy, which exists between an atom adjacent to a Mn atom and an Mn atom at an interatomic distance of 0.07 nm to 0.2 nm, is smaller than the peak at an oxygen partial pressure of 5.0 × 10 -1 After heat treatment in an atmosphere with a temperature of 500°C to 800°C or less at a temperature of 0.1 Pa or less, the interatomic distance shifts to a shorter one.

[0008] In the third embodiment, in the first embodiment, a peak in the radial distribution function that exists when the interatomic distance is between 0.07 nm and 0.2 nm shifts toward a shorter interatomic distance after heat treatment.

[0009] In a fourth aspect, in any one of the first to third aspects, the second oxide has a Rdolphin-Popper phase.

[0010] In a fifth aspect, in the fourth aspect, the crystal structure of the second oxide is represented by chemical formula A n+1 B n X 3n+1 When expressed as: the B site contains Ni.

[0011] In a sixth aspect, in the fifth aspect, the crystal structure of the first oxide is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains La, and the A site of the second oxide contains La.

[0012] A seventh embodiment is any one of the first to sixth embodiments, wherein the first oxide and the second oxide do not contain an alkali metal or an alkaline earth metal.

[0013] An eighth aspect is an air electrode including the air electrode catalyst according to any one of the first to seventh aspects.

[0014] A ninth aspect is an air secondary battery including the air electrode catalyst according to any one of the first to seventh aspects. Effect of the Invention

[0015] According to the present invention, it is estimated that the peaks existing between the interatomic distances of 0.34 nm and 0.39 nm and the peaks existing between the interatomic distances of 0.07 nm and 0.2 nm correspond to O atoms of the first oxide, and these peaks are in the range of 0.02 nm to 0.2 nm when the oxygen partial pressure is 5.0×10 -1 It is presumed that this affects the Mn-O atomic correlation of the first oxide, since the Mn-O atomic correlation decreases, disappears, or the interatomic distance shifts to a shorter value after heat treatment in an atmosphere at a temperature of 500°C to 800°C or less at a pressure of 500 Pa or less. As a result, the air electrode catalyst, air electrode, and air secondary battery can have a higher activity due to the first oxide per unit amount of catalyst than the activity per unit amount of the first oxide. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic diagram of an air secondary battery according to one embodiment. [Diagram 2] The |F(R)| spectrum was obtained by Fourier transform of the signal in the extended X-ray fine structure (EXAFS) region measured near the Mn K absorption edge of the catalyst. [Diagram 3] This is the |F(R)| spectrum where the interatomic distance is around 0.14 nm. [Figure 4] This is the |F(R)| spectrum where the interatomic distance is around 0.36 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Fig. 1 is a schematic diagram of an air secondary battery 10 in one embodiment. The air secondary battery 10 is a battery that uses oxygen in the air as the positive electrode active material, and includes an air electrode 11 (positive electrode) and a negative electrode 16. The air electrode 11 includes a gas diffusion layer 12 through which air (oxygen) diffuses, and a catalyst layer 14 in which an oxygen reduction reaction (ORR) occurs during discharge and an oxygen evolution reaction (OER) occurs during charge.

[0018] The gas diffusion layer 12 has a function of allowing air to pass through while preventing the intrusion of water from the outside air. The gas diffusion layer 12 is made of a sheet formed by mixing highly hydrophobic carbon such as acetylene black with a highly water-repellent polytetrafluoroethylene (PTFE) binder, a carbon mesh, a porous PTFE film, or the like. A current collector 13 is embedded in the gas diffusion layer 12. Examples of the current collector 13 include a metal mesh made of nickel or nickel-plated copper.

[0019] The catalyst layer 14 contains carbon with a high specific surface area, such as carbon black or activated carbon, a PTFE binder, and a catalyst 15 (catalyst for the air electrode). The negative electrode 16 is made of a metal containing, for example, Li, Zn, Al, Mg, Fe, etc., and has a function of generating ions in the electrolyte 18. The separator 17 electrically insulates the air electrode 11 (positive electrode) and the negative electrode 16, and also has a function of allowing the ions contained in the electrolyte 18 to pass through. The reaction in the catalyst layer 14 occurs at the three-phase interface between the solid phase (carbon and catalyst 15), the liquid phase (electrolyte 18), and the gas phase (oxygen).

[0020] The catalyst 15 includes a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide. The first oxide having a perovskite-type crystal structure is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains one or more elements selected from La, Ce, Pr, and Nd, and B contains Mn. In the first oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The first oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0021] The second oxide is not particularly limited, but examples thereof include oxides having a perovskite crystal structure, particularly layered perovskite oxides having the Ruddersden-Popper phase, and oxides having a spinel crystal structure. The second oxide having a perovskite crystal structure is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains one or more elements selected from La, Ce, Pr, and Nd, and B contains one or more elements selected from Cr, Mn, Fe, Co, and Ni. In the second oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0022] The layered perovskite oxide with the Ruddersden-Popper phase has a layered structure in which perovskite layers ABO3 and rock salt layers AO are layered alternately. The second oxide with the Ruddersden-Popper phase is represented by the chemical formula A n+1 B n X 3n+1 In this formula, the A site contains one or more elements selected from La, Ce, Pr, and Nd, B contains one or more elements selected from Cr, Mn, Fe, Co, and Ni, and X contains O. In the second oxide, a part of the elements in the A site and the B site may be replaced with one or more elements selected from transition metals such as Cr, Fe, Co, Ni, and Cu. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0023] When the second oxide having a spinel crystal structure is represented by the chemical formula AB2O4, the A site contains one or more selected from Mn, Zn, Fe, Mo, Cd, Ti, Ni, and Co, and the B site contains one or more selected from Cr, Al, Fe, Ni, Co, Mn, and V. The second oxide may contain an alkali metal or an alkaline earth metal in the A site.

[0024] The catalyst 15 is prepared by, for example, preparing a first oxide and a second oxide, mixing them, and then heating the mixture in a gas having an oxygen partial pressure of 5.0×10 -1The first oxide and the second oxide can be produced by heating to a temperature of 500°C to 800°C in a reducing atmosphere of less than Pa. The first oxide and the second oxide can be produced by a solid-phase method using thermal decomposition or solid-phase reaction, a liquid-phase method such as a precipitation method or a solvent evaporation method, or a gas-phase method such as a gas-phase reaction method or an evaporation-condensation method.

[0025] The particle size of the catalyst 15 is not particularly limited, but is exemplified as 2 nm to 10 μm. In order to utilize the activity of the first oxide and the activity of the second oxide, the volume ratio of the first oxide to the combined volume of the first oxide and the second oxide is preferably 20% to 80%.

[0026] The catalyst 15 may contain other elements or compounds in addition to the first oxide and the second oxide. Examples of the other elements include precious metals such as Pd, Pt, and Ag. Examples of the other compounds include oxides having a perovskite crystal structure that are different from the first oxide and the second oxide, phthalocyanine compounds, and porphyrin compounds. EXAMPLES

[0027] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0028] (Preparation of the first oxide) La(OH)3 and Mn2O3 (both of special reagent grade) were weighed out to obtain LaMnO3, and the weighed raw materials and ethanol were placed in an alumina pot together with zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried, then placed in an alumina crucible and fired at 1000°C. The fired powder and ethanol were placed in an alumina pot together with zirconia balls, and were ground in a ball mill for 15 hours. The slurry removed from the pot was dried, then ground in a mortar to obtain a powder (first oxide). The obtained powder was confirmed to be LaMnO3 with a perovskite-type crystal structure by powder X-ray diffraction (XRD).

[0029] (Preparation of the Second Oxide) La(OH)3 and NiO (both of special reagent grade) were weighed out to obtain La2NiO4, and the weighed raw materials and ethanol were placed in an alumina pot together with zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried, then placed in an alumina crucible and fired at 1000°C. The fired powder and ethanol were placed in an alumina pot together with zirconia balls, and were ground in a ball mill for 15 hours. The slurry removed from the pot was dried, then ground in a mortar to obtain a powder. The obtained powder (second oxide) was confirmed by XRD to be La2NiO4, a layered perovskite oxide with the Ruddersden-Popper phase.

[0030] (Preparation of Catalyst in Example 1) The same volumes of the first oxide and the second oxide (first oxide:second oxide = 1:1 (volume ratio)) were placed in an alumina pot together with ethanol and zirconia balls, and were mixed and ground in a ball mill for 15 hours. The slurry removed from the pot was dried and then ground in a mortar to obtain a powder. The oxygen partial pressure was 5.0 x 10 -1 The powder was heated from room temperature to 500° C. under a nitrogen atmosphere of 100 Pa, heated at 500° C. for 1 hour, and then cooled from 500° C. to room temperature. This resulted in the catalyst of Example 1 in which the first oxide and the second oxide were combined.

[0031] (Catalyst in Example 2) Oxygen partial pressure is 5.0 x 10 -1 The catalyst in Example 2, in which the first oxide and the second oxide were combined, was obtained in the same manner as in Example 1, except that the powder was heated from room temperature to 800°C under a nitrogen atmosphere of 1 Pa, heated at 800°C for 1 hour, and then cooled from 800°C to room temperature.

[0032] (Catalyst in Reference Example 1) The first oxide was used as the catalyst in Reference Example 1.

[0033] (Preparation of Catalyst in Reference Example 2) Oxygen partial pressure is 5.0 x 10 -1The first oxide was heated from room temperature to 500° C. under a nitrogen atmosphere of 1 Pa, heated at 500° C. for 1 hour, and cooled from 500° C. to room temperature. In this way, a catalyst in Reference Example 2 was obtained.

[0034] (Preparation of Catalyst in Reference Example 3) Oxygen partial pressure is 5.0 x 10 -1 The first oxide was heated from room temperature to 800° C. under a nitrogen atmosphere of 10 Pa, heated at 800° C. for 1 hour, and then cooled from 800° C. to room temperature. In this way, a catalyst in Reference Example 3 was obtained.

[0035] (Preparation of Catalyst in Reference Example 4) The first oxide and the second oxide, each having the same volume, were placed in an alumina pot together with ethanol and zirconia balls, and were mixed and ground in a ball mill for 15 hours. The slurry taken out of the pot was dried and then ground in a mortar to obtain a catalyst in Reference Example 4.

[0036] The specific surface area of ​​the catalysts in Examples 1 and 2 and Reference Examples 1 to 4 was 3.5 m 2 / g to 5.0m 2 / g range.

[0037] (Preparation of ink for producing air electrodes) A 5 wt% Nafion dispersion solution (Fujifilm Wako DE521) was mixed with a KOH (0.1M) aqueous solution to prepare a 3.33 wt% Nafion dispersion solution, and then 1-propanol (Fujifilm Wako) was added to this dispersion solution to prepare a solution. Each of the catalysts in Examples 1 and 2 and Reference Examples 1-4 and acetylene black (Denka Li-250), which is a conductive material, were dispersed in this solution to prepare six types of ink. The ratio (mass ratio) of catalyst, conductive material, and Nafion in the ink was catalyst:conductive material:Nafion=5:1:1. The six types of inks prepared were applied to a rotating disk electrode at approximately 250 μg / cm. 2 The catalyst was then evaporated to dryness at room temperature to obtain six types of electrodes intended as air electrodes.

[0038] (Electrochemical measurements) Electrochemical measurements were performed using a rotating disk electrode apparatus (BAS RRDE-3A) to evaluate the ORR activity of the electrode (air electrode). A rotating disk electrode (RDE) was used as the working electrode, Hg / HgO (internal solution was 0.1 M KOH aqueous solution) was used as the reference electrode, and a Pt coil was used as the counter electrode in an oxygen-saturated 0.1 M KOH aqueous solution. First, cyclic voltammetry (CV) was performed using a potentiostat, and the potential was swept from 1.0 to 0.0 V relative to the reversible hydrogen electrode (RHE) at 100 mV / s for 30 cycles. Linear sweep voltammetry (LSV) was then performed, and the current was measured when the potential was swept from 1.0 to 0.0 V relative to the RHE at 10 mV / s. During the measurements, the RDE was rotated at 1600 rpm to prevent charge transfer rate limitation and the adhesion of air bubbles. From the results of the current measurements using LSV, the surface area of ​​the electrode was determined to be 0.126 cm 2 The current density is 0.4mA / cm 2 The potential was calculated at this time and the results are shown in Table 1.

[0039] [Table 1]

[0040] Since the higher the potential, the higher the ORR activity, according to Table 1, the order of highest ORR activity was Example 2, Example 1, Reference Example 3, Reference Example 2, Reference Example 1, and Reference Example 4. It was confirmed that the ORR activity of the catalysts in Examples 1 and 2 in which LaMnO3 and La2NiO4 were combined was higher than the ORR activity of LaMnO3 alone (Reference Examples 1 to 3).

[0041] (X-ray absorption fine structure analysis) The spectra in the extended X-ray fine structure (EXAFS) region were measured near the Mn K absorption edge of the catalysts in Examples 1 and 2 and Reference Examples 1 to 4 by X-ray absorption spectroscopy, and a Fourier transform was performed within the range of a set window function to obtain a radial distribution function. Figure 2 shows the |F(R)| spectrum (radial distribution function) obtained by Fourier transform of the signal in the EXAFS region measured near the Mn K absorption edge of the catalysts in Examples 1 and 2.

[0042] 2, the radial distribution function in Example 1 had peaks at interatomic distances of about 0.14 nm, about 0.2 nm, about 0.25 nm, about 0.3 nm, and about 0.36 nm. The radial distribution function in Example 2 had peaks at interatomic distances of about 0.14 nm, about 0.2 nm, about 0.25 nm, and about 0.3 nm. The peak near 0.36 nm seen in the radial distribution function in Example 1 disappeared in the radial distribution function in Example 2.

[0043] Fig. 3 is a spectrum of the radial distribution function in Examples 1 and 2 and Reference Examples 1 to 4, enlarging the area around the interatomic distance of 0.14 nm. Fig. 4 is a spectrum of the radial distribution function in Examples 1 and 2 and Reference Examples 1 to 4, enlarging the area around the interatomic distance of 0.36 nm. As a result of comparing the lattice spacing and peak positions of known reference data of the catalyst structure identified by XRD, it was estimated that both the peaks existing between Mn atoms and the interatomic distance of 0.07 nm to 0.2 nm and the peaks existing between Mn atoms and the interatomic distance of 0.34 nm to 0.39 nm were derived from O atoms.

[0044] In FIG. 3, the peak of Reference Example 1, the catalyst of Reference Example 1 was used at an oxygen partial pressure of 5.0×10 -1 The peak of Reference Example 2, which was heat-treated at 500° C. under an atmosphere of 1.0×10 Pa, and the peak of Reference Example 3, which was heat-treated at 800° C. under the same atmosphere, shifted toward a longer interatomic distance. -1 The peak of Example 1 heat-treated at 500° C. under an atmosphere of 100 Pa and the peak of Example 2 heat-treated at 800° C. under the same atmosphere shifted toward shorter interatomic distances. Furthermore, the peaks of Examples 1 and 2 were weaker in intensity than the peak of Reference Example 4.

[0045] The peak shift toward shorter interatomic distances in Examples 1 and 2 was presumed to be due to the effect of the interaction between LaMnO3 and La2NiO4 on the Mn-O interatomic correlation of LaMnO3. The high ORR activity in Examples 1 and 2 was presumed to be related to the peak shift.

[0046] In FIG. 4, the peaks of Examples 1 and 2 were smaller than that of Reference Example 4. In particular, the peak corresponding to the peak of Reference Example 4 disappeared in Example 1. Since the peak was presumed to be derived from O atoms, there was a possibility that the deficiency of O atoms increased in Examples 1 and 2. It was presumed that the high ORR activity of Examples 1 and 2 was related to the reduction or disappearance of the peak.

[0047] In Examples 1 and 2, La2NiO4 composited with LaMnO3 is a layered perovskite oxide having a Ruddlesden-Popper phase, and it was presumed that O atoms resulting from the loss of O atoms in LaMnO3 may have been incorporated between the layers. In the catalysts in Examples 1 and 2, LaMnO3 (first oxide) having a perovskite-type crystal structure containing Mn and La2NiO4 (second oxide) having a perovskite-type crystal structure having a Ruddlesden-Popper phase were composited, and it was presumed that exchange of O atoms was facilitated between the first oxide and the second oxide.

[0048] The catalysts in Examples 1 and 2 were subjected to an oxygen partial pressure of 5.0×10 -1 After heat treatment at 500°C or 800°C in a nitrogen atmosphere of 10 Pa, the |F(R)| spectrum was obtained by Fourier transform of the signal in the EXAFS region measured near the Mn K absorption edge of the catalyst. When compared with the |F(R)| spectrum before heat treatment, the peaks existing between the Mn atoms at an interatomic distance of 0.07 nm to 0.2 nm shifted toward shorter interatomic distances, and the peaks existing between the Mn atoms at an interatomic distance of 0.34 nm to 0.39 nm became lower or disappeared. Therefore, it was revealed that the shift in peaks, the decrease in intensity, or the disappearance of peaks before and after heat treatment are characteristics of the catalysts in Examples 1 and 2.

[0049] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0050] In the examples, the catalyst in Example 2 has been described as having a peak disappearing that corresponds to the peak in Reference Example 4 at an interatomic distance of about 0.36 nm, but this is not necessarily limited to this. Depending on the state of mixing the first oxide and the second oxide, the particle size, etc., the catalyst in Example 2 may have a reduced intensity of the peak corresponding to the peak in Reference Example 4 (the peak does not disappear).

[0051] In the embodiment, the catalyst 15 arranged in the air electrode 11 of the air secondary battery 10 has been described as an example, but this is not necessarily limited to this. It is of course possible to arrange the catalyst 15 in other air electrodes. Examples of other air electrodes include air electrodes of fuel cells and air electrodes of water electrolysis. [Explanation of symbols]

[0052] 10. Air secondary battery 11 Air electrode 15 Catalyst (air electrode catalyst)

Claims

1. A catalyst for an air electrode, comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, In the radial distribution function obtained by X-ray absorption spectroscopy, a peak exists when the interatomic distance between the Mn atom and an atom adjacent to the Mn atom is between 0.34 nm and 0.39 nm, and the oxygen partial pressure of the air electrode catalyst is 5.0 × 10 -1 The catalyst for an air electrode is reduced or disappears after heat treatment in an atmosphere having a pressure of 500 to 800° C. and a pressure of 500 to 800° C. or less.

2. A catalyst for an air electrode, comprising a first oxide having a perovskite-type crystal structure containing Mn, and a second oxide, In the radial distribution function obtained by X-ray absorption spectroscopy, a peak exists when the interatomic distance between the Mn atom and an atom adjacent to the Mn atom is between 0.07 nm and 0.2 nm, and the oxygen partial pressure of the air electrode catalyst is 5.0 × 10 -1 The air electrode catalyst shifts the interatomic distance to a shorter value after heat treatment in an atmosphere at a pressure of 500° C. or more and a temperature of 500° C. or more and 800° C. or less.

3. 2. The air electrode catalyst according to claim 1, wherein a peak in the radial distribution function that exists when the interatomic distance is between 0.07 nm and 0.2 nm shifts to a direction in which the interatomic distance becomes shorter after the heat treatment.

4. 4. The air electrode catalyst according to claim 1, wherein the second oxide has a Rudolfden-Popper phase.

5. The crystal structure of the second oxide is represented by chemical formula A n+1 B n X 3n+1 5. The air electrode catalyst according to claim 4, wherein the B site contains Ni.

6. The crystal structure of the first oxide is represented by the chemical formula ABO 3-δ When expressed as (δ≦0.4), the A site contains La, 6. The air electrode catalyst according to claim 5, wherein the A site of the second oxide contains La.

7. 4. The air electrode catalyst according to claim 1, wherein the first oxide and the second oxide do not contain an alkali metal or an alkaline earth metal.

8. An air electrode of an air secondary battery, comprising the air electrode catalyst according to claim 1 .

9. An air secondary battery comprising the air electrode catalyst according to claim 1 .

Citation Information

Patent Citations

  • Electrode for secondary battery

    JP2005190833A